Women's Mental Health in the Time of Covid-19 Pandemic - Thibaut, Florence; van Wijngaarden-Cremers, Patricia J. M. (Frontiers in Global Women's Health, 2020)
Even if the fatality rate for men has been twice higher than for women, Covid-19 pandemic has affected women much more profoundly, both as frontline workers and at home. The specific situation of pregnancy during the pandemic will be also discussed. In addition, home is unfortunately not always a safe space. Many countries have reported an increase in domestic violence cases after the viral outbreak. Gender-based violence is exacerbated by these conditions but may not receive the attention it needs in the drive to respond to the pandemic. It is also noteworthy that the risk of anxiety, depression and PTSD following exposure to trauma is much higher in women. We should consider this pandemic as an opportunity to build better, stronger, resilient societies that could bring both relief and hope to all women around the world.